Anti-biofilm potential and mode of action of Malaysian plant species: a review / Nur Anisah Johari ... [et al.] - Johari, Nur Anisah; Amran, Siti Sarah Diyana; Che Man, Che Amira Izzati; Raja Yahaya, Mohd Fakharul Zaman; Kamaruzzaman, Alya Nur Athirah (Faculty of Applied Sciences, 2020)
Biofilm is a microbial community that attaches to a surface and is enclosed in extracellular polymeric substance (EPS) matrix. Formation of biofilm often develops resistance towards a wide spectrum of antimicrobial agents. Since the biofilm-mediated diseases are commonly difficult to treat, there is a need to find new antibiofilm agent. The studies on antibiofilm activities of plant species have received a great deal of attention over the last few decades. In Malaysia, plant species have been used as alternatives to the conventional antimicrobial therapy. Several Malaysian plant species are known to control biofilm infection by inhibition of quorum sensing pathway, disruption of EPS matrix, alteration of cell permeability and reduction in cell surface hydrophobicity. This review demonstrates that Malaysian plant species may become excellent therapeutic agents in combating the biofilm infection.